Molecular modification, expression and purification of new subtype antioxidant peptide from Pinctada fucata by recombinant Escherichia coli to improve antioxidant-activity - Wu, Yanyan (J Food Sci Technol, 2018)
The aim of this study was to establish a system for the efficient expression and purification of new subtype of antioxidant peptide from Pinctada fucata meat (NPFMAP), which is designed by molecular modification technology based on the sequence of purified and identified antioxidant peptide from Pinctada fucata meat (PFMAP, Gly-Ala-Gly-Leu-Pro-Gly-Lys-Arg-Glu-Arg), and to better understand the relationship between structure and antioxidant activity. Meanwhile, gene codon usage was optimized and the glutathione S-transferase (GST) tag of pGEX-6P-1 was added to facilitate expression and purification NPFMAP in Escherichia coli. The results of antioxidant activity assay in vitro showed a higher antioxidant activity in NPFMAP than that in enzymatic hydrolysis digested or chemically synthesized PFMAP. In particular, the DPPH scavenging radical activity increased by about 4.7 times after molecular modification. Structural bioanalysis indicated that new subtype antioxidant peptide had spatial conformation and good hydrophilic after modification, which was confirmed by antioxidant activity assays. Thus, the proposed method could be used to obtain NPFMAP with high antioxidant activity.